Synthesis and characterization of water-soluble C60–peptide conjugates - Ma, Yue; Persi, Lorenzo; Yamakoshi, Yoko (Beilstein Journal of Organic Chemistry, 2024)
With the aim of developing biocompatible and water-soluble C60 derivatives, three types of C60–peptide conjugates consisting of hydrophilic oligopeptide anchors (oligo-Lys, oligo-Glu, and oligo-Arg) were synthesized. A previously reported Prato reaction adduct of a biscarboxylic acid-substituted C60 derivative was subjected to a solid phase synthesis for amide formation with N-terminal amines of peptides on resin to successfully provide C60–peptide conjugates with one C60 and two peptide anchors as water-soluble moieties. Among three C60–peptide conjugates prepared, C60–oligo-Lys was soluble in water at neutral pH, and C60–oligo-Glu was soluble in buffer with a higher pH value, but C60–oligo-Arg was insoluble in water and most other solvents. C60–oligo-Lys and C60–oligo-Glu were characterized by 1H and 13C NMR. Photoinduced 1O2 generation was observed in the most soluble C60–oligo-Lys conjugate under visible light irradiation (527 nm) to show the potential of this highly water-soluble molecule in biological systems, for example, as a photosensitizer in photodynamic therapy.
Keywords: biomaterial; fullerene; peptide; water-soluble